Nest-shaped P, Fe-NiMoO4 self-supporting electrode material and preparation method thereof
By growing the P,Fe-co-doped NiMoO4 nanowire network structure in situ on nickel foam, forming a nest-like self-supporting electrode material, the problems of poor conductivity and limited active edge sites of the existing NiMoO4 electrode materials are solved, and the problem of poor conductivity and limited active edge sites are achieved. Efficient electrocatalytic oxidation effect.
Patent Information
- Application Number
- CN202310969338.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
The existing NiMoO4 electrode materials have poor conductivity and limited active edge sites, which limit their commercial application in electrocatalytic oxidation.
The P,Fe-co-doped NiMoO4 nanowire network structure was used to grow in situ on the foam nickel to form a self-supporting electrode material with a nest-like open structure.
The electrocatalytic oxidation efficiency is improved, the charge transport and material transfer capabilities are enhanced, and the catalytic activity and stability are significantly improved.
Smart Images

Figure CN119433591A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrode materials, and relates to a bird's nest-shaped P, Fe-NiMoO4 nickel foam electrode material and a preparation method thereof, and specifically relates to a bird's nest-shaped P, Fe-NiMoO4 self-supporting electrode material for electrocatalytic oxidation of aqueous solution and a preparation method thereof. Background Art
[0002] In order to develop a low-carbon economy, using renewable energy to split water to produce hydrogen is an effective way. Water electrolysis includes water reduction hydrogen evolution reaction (HER) and water oxidation oxygen evolution reaction (OER), in which the slow kinetics of OER on the anode side significantly reduces the water splitting efficiency. Therefore, it is still a huge challenge to design efficient catalysts to promote the catalytic reaction kinetics of OER. At present, IrO2 and RuO2 show remarkable performance in oxygen production due to their favorable electronic structures. However, their scarcity, high cost and poor stability have seriously hindered their application in electrocatalytic water splitting. Therefore, there is an urgent need to develop non-precious metal catalysts with excellent chemical activity and chemical stability.
[0003] NiMoO4 is a promising candidate for OER catalyst due to its low cost, moderate intrinsic activity and easy structural optimization. However, NiMoO4 has disadvantages such as poor conductivity and few active sites, which limit their commercial application in electrocatalytic water splitting. At present, regulating the electronic structure by doping is an effective way to further improve the catalytic performance. At the same time, open-pore micro-nanostructures with high specific surface area can produce abundant catalytic active sites and accelerate charge transport and material transfer. However, the currently prepared NiMoO4 materials have poor conductivity, limited active edge sites and low activity, which limits their commercial application in electrocatalytic oxidation.
[0004] Based on the above reasons, how to find a preparation process to obtain NiMoO4 electrode material with good conductivity, significant catalytic activity and good stability is the key problem to be solved by the present invention. Summary of the invention
[0005] The purpose of the present invention is to provide a bird's nest-shaped P, Fe-NiMoO4 self-supporting electrode material and a preparation method thereof, which overcomes the disadvantages of the NiMoO4 material prepared in the prior art that the morphology is difficult to control, toxic and harmful solvents need to be used, it is difficult to achieve co-doping of non-metallic elements and metal elements, and the conductivity is poor, the active edge sites are limited, and the activity is low. The method is simple in process, and the prepared bird's nest-shaped P, Fe-NiMoO4 self-supporting electrode material is a P, Fe-co-doped NiMoO4 nanowire network structure in situ grown on nickel foam, and has high electrocatalytic performance. The present invention adopts the following technical solutions to achieve this:
[0006] A bird's nest-shaped P, Fe-NiMoO4 self-supporting electrode material and a preparation method thereof, characterized in that the electrode material is a bird's nest-shaped open structure P, Fe-NiMoO4 composed of a P, Fe-co-doped NiMoO4 nanowire network grown in situ on nickel foam metal, and the electrode material can be used for electrocatalytic oxidation oxygen evolution reaction of water and urea oxidation reaction in aqueous solution, and the preparation method comprises the following steps:
[0007] (1) Place nickel foam (1-10*1-10cm 2 )Use 1-3 mol·L -1 Ultrasonic treatment with dilute hydrochloric acid for 1-10 min, then treatment with acetone for 1-10 min, then washing with ethanol and drying;
[0008] (2) (NH4)6Mo7O 24 ·4H2O and FeCl3·6H2O are dissolved in water and stirred evenly. (NH4)6Mo7O 24 4H2O concentration is 1-50mmol·L -1 , FeCl3·6H2O concentration is 10-100mmol·L -1 ;
[0009] (3) The mixed solution obtained in step 2 is transferred to a polytetrafluoroethylene-lined autoclave, the nickel foam metal sheet treated in step 1 is placed vertically in the solution, and then reacted at 100-200° C. for 3-24 hours. After the autoclave is naturally cooled to room temperature, the nickel foam metal sheet is taken out, washed three times with deionized water and ethanol respectively, and dried to obtain a Fe-NiMoO4 sample;
[0010] (4) In a tubular furnace, the Fe-NiMoO4 sample obtained in step (3) is placed in a porcelain boat, 0.1-2 g NaH2PO2·H2O is placed in another porcelain boat and placed upstream of the carrier gas, the tubular furnace is sealed, nitrogen carrier gas is introduced from one end, the temperature is increased to 250-450°C at a heating rate of 1-15°C / min, and the temperature is kept for 1-4 h to obtain a P,Fe-NiMoO4 sample.
[0011] The advantages of the present invention are: the bird's nest structure composed of the P, Fe-co-doped NiMoO4 nanowire network grows in situ on the nickel foam to form a self-supporting electrode material, which is conducive to material transfer and charge transmission, promotes bubble overflow, and improves working stability; at the same time, P, Fe-co-doping can increase the charge transfer ability, expose more active sites, adjust the electronic configuration of the catalyst, and is conducive to optimizing the adsorption energy of the reactant intermediate, thereby greatly improving the catalytic oxidation efficiency. It is used for efficient electrocatalytic oxidation of water to produce oxygen, and the electrocatalytic oxidation of urea, hydrogen sulfide and organic dyes in aqueous solution has high activity and stable performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 The X-ray powder diffraction (XRD) spectrum of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention.
[0013] Figure 2 This is a scanning electron microscope (SEM) photograph of a bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention.
[0014] Figure 3 Transmission electron microscope (TEM) photograph of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention.
[0015] Figure 4 The STEM-HAADF photograph and the corresponding element distribution diagram of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention.
[0016] Figure 5 The OER performance test results of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material and the comparative electrode material prepared by the method described in Example 1 of the present invention.
[0017] Figure 6 The OER cycle stability test results of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention.
[0018] Figure 7 The urea electro-oxidation performance test results of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention and the comparative example electrode material are shown. DETAILED DESCRIPTION
[0019] Embodiment 1:
[0020] (1) Place nickel foam (2*3cm 2 ) with 2 mol·L -1 Ultrasonic treatment with dilute hydrochloric acid for 2 min, then treatment with acetone for 2 min, then washing with ethanol and drying;
[0021] (2) (NH4)6Mo7O 24 ·4H2O and FeCl3·6H2O are dissolved in water and stirred evenly. (NH4)6Mo7O 24 4H2O concentration is 4.6mmol·L -1 , FeCl3·6H2O concentration is 52.8mmol·L-1 ;
[0022] (3) The mixed solution obtained in step 2 is transferred to a polytetrafluoroethylene-lined autoclave, the nickel foam metal sheet treated in step 1 is placed vertically in the solution, and then reacted at 150° C. for 10 h. After the autoclave is naturally cooled to room temperature, the nickel foam metal sheet is taken out, washed three times with deionized water and ethanol respectively, and dried to obtain a Fe-NiMoO4 sample;
[0023] (4) In a tubular furnace, the Fe-NiMoO4 sample obtained in step (3) is placed in a porcelain boat, and 0.2 g of NaH2PO2·H2O is placed in another porcelain boat and placed upstream of the carrier gas. The tubular furnace is sealed, and nitrogen carrier gas is introduced from one end. The temperature is increased to 300°C at a heating rate of 5°C / min and kept at this temperature for 4 h to obtain a P,Fe-NiMoO4 sample.
[0024] Embodiment 2:
[0025] (1) Place nickel foam (1*1cm 2 ) using 1 mol·L -1 Ultrasonic treatment with dilute hydrochloric acid for 1 min, then treatment with acetone for 1 min, then washing with ethanol and drying;
[0026] (2) (NH4)6Mo7O 24 ·4H2O and FeCl3·6H2O are dissolved in water, stirred evenly, (NH4)6Mo7O 24 4H2O concentration: 1mmol·L -1 mmol·L -1 , FeCl3·6H2O concentration: 10mmol·L -1 ;
[0027] (3) The mixed solution obtained in step 2 is transferred to a polytetrafluoroethylene-lined autoclave, and the nickel foam treated in step 1 is vertically placed therein, and then reacted at 100° C. for 24 hours. After the reaction, it is naturally cooled to room temperature, washed three times with deionized water and ethanol respectively, and dried to obtain a Fe-NiMoO4 sample;
[0028] (4) The sample obtained in step (3) is placed in a porcelain boat, which is then placed in a tubular furnace. 0.1 g of NaH2PO2·H2O is placed in another porcelain boat, which is then placed in the tubular furnace and positioned upstream. The tubular furnace is sealed, and nitrogen carrier gas is introduced from one end. The temperature is increased to 250°C at a rate of 1°C / min and maintained for 4 h to obtain a P,Fe-NiMoO4 sample.
[0029] Embodiment three:
[0030] (1) Place nickel foam (10*10cm2 ) with 3 mol·L -1 Ultrasonic treatment with dilute hydrochloric acid for 10 min, then treatment with acetone for 10 min, then washing with ethanol and drying;
[0031] (2) (NH4)6Mo7O 24 ·4H2O and FeCl3·6H2O are dissolved in water, stirred evenly, (NH4)6Mo7O 24 4H2O concentration: 50mmol·L -1 mmol·L -1 , FeCl3·6H2O concentration: 100mmol·L -1 ;
[0032] (3) The mixed solution obtained in step 2 is transferred to a polytetrafluoroethylene-lined autoclave, and the nickel foam treated in step 1 is vertically placed therein, and then reacted at 200° C. for 3 h. After the reaction, it is naturally cooled to room temperature, washed with deionized water and ethanol three times each, and dried to obtain a Fe-NiMoO4 sample;
[0033] (4) The sample obtained in step (3) is placed in a porcelain boat, which is then placed in a tubular furnace. 2 g of NaH2PO2·H2O is placed in another porcelain boat, which is then placed in the tubular furnace and positioned upstream. The tubular furnace is sealed, and nitrogen carrier gas is introduced from one end. The temperature is increased to 450°C at a rate of 15°C / min and maintained for 1 h to obtain a P,Fe-NiMoO4 sample.
[0034] Embodiment 4:
[0035] (1) Place nickel foam (2*3cm 2 ) using 1 mol·L -1 Ultrasonic treatment with dilute hydrochloric acid for 3 min, then treatment with acetone for 3 min, then washing with ethanol and drying;
[0036] (2) (NH4)6Mo7O 24 ·4H2O and FeCl3·6H2O are dissolved in water, stirred evenly, (NH4)6Mo7O 24 4H2O concentration: 10mmol·L -1 mmol·L -1 , FeCl3·6H2O concentration: 52.8mmol·L -1 ;
[0037] (3) The mixed solution obtained in step 2 is transferred to a polytetrafluoroethylene-lined autoclave, and the nickel foam treated in step 1 is vertically placed therein, and then reacted at 150° C. for 10 h. After the reaction, it is naturally cooled to room temperature, washed with deionized water and ethanol three times each, and dried to obtain a Fe-NiMoO4 sample;
[0038] (4) The sample obtained in step (3) is placed in a porcelain boat, which is then placed in a tube furnace. 0.5 g of NaH2PO2·H2O is placed in another porcelain boat, which is then placed in the tube furnace and positioned upstream. The tube furnace is sealed, nitrogen is passed through, and the temperature is increased to 350°C at a rate of 1-15°C / min, and the temperature is maintained for 2 h to obtain a P,Fe-NiMoO4 sample.
[0039] Embodiment five:
[0040] (1) Place nickel foam (5*5cm 2 ) using 1 mol·L -1 Ultrasonic treatment with dilute hydrochloric acid for 3 min, then treatment with acetone for 3 min, then washing with ethanol and drying;
[0041] (2) (NH4)6Mo7O 24 ·4H2O and FeCl3·6H2O are dissolved in water, stirred evenly, (NH4)6Mo7O 24 4H2O concentration: 4.6mmol·L -1 mmol·L -1 , FeCl3·6H2O concentration: 52.8mmol·L -1 ;
[0042] (3) The mixed solution obtained in step 2 is transferred to a polytetrafluoroethylene-lined autoclave, and the nickel foam treated in step 1 is vertically placed therein, and then reacted at 180° C. for 6 h. After the reaction, it is naturally cooled to room temperature, washed with deionized water and ethanol three times each, and dried to obtain a Fe-NiMoO4 sample;
[0043] (4) The sample obtained in step (3) is placed in a porcelain boat, which is then placed in a tubular furnace. 0.4 g of NaH2PO2·H2O is placed in another porcelain boat, which is then placed in the tubular furnace and positioned upstream. The tubular furnace is sealed, nitrogen is passed through, and the temperature is increased to 300°C at a rate of 10°C / min and maintained for 2 h to obtain a P,Fe-NiMoO4 sample.
[0044] Embodiment six:
[0045] (1) Place nickel foam (2*3cm 2 ) with 2 mol·L -1Ultrasonic treatment with dilute hydrochloric acid for 5 min, then treatment with acetone for 5 min, then washing with ethanol and drying;
[0046] (2) (NH4)6Mo7O 24 ·4H2O and FeCl3·6H2O are dissolved in water, stirred evenly, (NH4)6Mo7O 24 4H2O concentration: 13.8mmol·L -1 mmol·L -1 , FeCl3·6H2O concentration: 52.8mmol·L -1 ;
[0047] (3) The mixed solution obtained in step 2 is transferred to a polytetrafluoroethylene-lined autoclave, and the nickel foam treated in step 1 is vertically placed therein, and then reacted at 150° C. for 16 h. After the reaction, it is naturally cooled to room temperature, washed three times with deionized water and ethanol respectively, and dried to obtain a Fe-NiMoO4 sample;
[0048] (4) The sample obtained in step (3) is placed in a porcelain boat, which is then placed in a tubular furnace. 0.2 g of NaH2PO2·H2O is placed in another porcelain boat, which is then placed in the tubular furnace and positioned upstream. The tubular furnace is sealed, nitrogen is passed through, and the temperature is increased to 300°C at a rate of 2°C / min and maintained for 3 h to obtain a P,Fe-NiMoO4 sample.
[0049] Embodiment seven:
[0050] (1) Place nickel foam (10*10cm 2 ) using 1 mol·L -1 Ultrasonic treatment with dilute hydrochloric acid for 3 min, then treatment with acetone for 3 min, then washing with ethanol and drying;
[0051] (2) (NH4)6Mo7O 24 ·4H2O and FeCl3·6H2O are dissolved in water, stirred evenly, (NH4)6Mo7O 24 4H2O concentration: 50mmol·L -1 mmol·L -1 , FeCl3·6H2O concentration: 10mmol·L -1 ;
[0052] (3) The mixed solution obtained in step 2 is transferred to a polytetrafluoroethylene-lined autoclave, and the nickel foam treated in step 1 is vertically placed therein, and then reacted at 120° C. for 12 h. After the reaction, it is naturally cooled to room temperature, washed three times with deionized water and ethanol respectively, and dried to obtain a Fe-NiMoO4 sample;
[0053] (4) The sample obtained in step (3) is placed in a porcelain boat, which is then placed in a tubular furnace. 0.6 g of NaH2PO2·H2O is placed in another porcelain boat, which is then placed in the tubular furnace and positioned upstream. The tubular furnace is sealed, nitrogen is passed through, and the temperature is increased to 350°C at a rate of 10°C / min and maintained for 2 h to obtain a P,Fe-NiMoO4 sample.
[0054] Comparative Example 1:
[0055] (1) Place nickel foam (2*3cm 2 ) with 2 mol·L -1 Ultrasonic treatment with dilute hydrochloric acid for 2 min, then treatment with acetone for 2 min, then washing with ethanol and drying;
[0056] (2) (NH4)6Mo7O 24 ·4H2O and FeCl3·6H2O are dissolved in water and stirred evenly. (NH4)6Mo7O 24 4H2O concentration is 4.6mmol·L -1 , FeCl3·6H2O concentration is 52.8mmol·L -1 ;
[0057] (3) The mixed solution obtained in step 2 is transferred to a polytetrafluoroethylene-lined autoclave, the nickel foam metal sheet treated in step 1 is placed vertically in the solution, and then reacted at 150° C. for 10 hours. After the autoclave is naturally cooled to room temperature, the nickel foam metal sheet is taken out, washed three times with deionized water and ethanol respectively, and dried to obtain a Fe-NiMoO4 self-supporting electrode material; Comparative Example 2:
[0058] (1) Place nickel foam (2*3cm 2 ) with 2 mol·L -1 Ultrasonic treatment with dilute hydrochloric acid for 2 min, then treatment with acetone for 2 min, then washing with ethanol and drying;
[0059] (2) 10 mg of commercial IrO2 powder was ultrasonically treated for 30 min in a mixture of 30 μL Nafion solution, 450 μL deionized water and 550 μL ethanol to form a uniform dispersion. Next, 100 μL of the dispersion was evenly applied to the nickel foam pretreated in step (1) and dried naturally to obtain an IrO2 / nickel foam electrode.
[0060] Comparative Example 3
[0061] Put the nickel foam (2*3cm 2 ) with 2 mol·L -1 The nickel foam electrode was obtained by ultrasonic treatment with dilute hydrochloric acid for 2 min, then treated with acetone for 2 min, washed with ethanol and dried.
[0062] Figure 1 The X-ray powder diffraction (XRD) spectrum of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention. Figure 1 The diffraction peaks at 44.5°, 51.8°, and 76.3° in a correspond to the (111)(200)(220) crystal planes of nickel foam (PDF#04-0850). The diffraction peak at 26.5° corresponds to the (11-2) crystal plane of NiMoO4 (PDF#45-0142), indicating that the obtained sample contains NiMoO4. In addition, Figure 1 b is Figure 1 The local enlarged image around 26.5° in a, from Figure 1 b It can be seen that the (11-2) crystal plane of NiMoO4 in P,Fe-NiMoO4 / NF is shifted to a lower angle compared with the standard card of NiMoO4. This is due to the Fe 3+ Doped into the lattice to replace Ni 2+ At the same time, phosphorus ions are doped into the lattice to replace oxygen ions - position, because Fe 3+ The radius is Ni 2+ The radius of the phosphorus ion is larger than that of the oxygen ion, which leads to a larger unit cell. 4 / The diffraction peaks of NF can be indexed to NiMoO4, which indicates that the introduction of phosphorus and iron ions into the lattice does not significantly change the crystal structure.
[0063] Figure 2 This is a scanning electron microscope (SEM) photograph of a bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention. Figure 2 As can be seen from a, the P,Fe-co-doped NiMoO4 nanowire network structure is uniformly grown on the surface of the three-dimensional network structure of the nickel foam skeleton. Figure 2 b From the enlarged photo, it can be seen that a large number of nanowire edges and P, Fe-co-doping increase the active sites of the electrode material, which is beneficial to the improvement of conductivity; the porous structure expands the interface area of the electrode / electrolyte, as well as mass transfer and promotes fast charging, all of which contribute to the improvement of electrocatalytic activity.
[0064] Figure 3 Transmission electron microscope (TEM) photo of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention. Figure 3aIt can be seen that the in-situ grown bird's nest-like P, Fe-co-doped NiMoO4 is composed of a network structure interwoven with nanowires. The P, Fe-co-doped NiMoO4 nanowire network structure is assembled by many P, Fe-co-doped NiMoO4 quantum dots and presents a one-dimensional structure, which is conducive to the regulation of electronic structure and promotes the improvement of electrocatalytic activity. Figure 3b The high-magnification TEM images in the figure show that the microstructure of P-Fe-NiMoO4 and the spherical flower-like structure of the sample were further confirmed. The contrast between the spherical flower-like structure and the dark and bright contrast in the middle indicate that the flower-like spatial network structure of the sample is formed by cross-linking of nanosheets. The rough surface of the nanoflower formed by this cross-linking can expose more active sites and increase the activity of the reaction.
[0065] Figure 4 The STEM-HAADF photo and the corresponding element distribution diagram of the bird's nest-like P, Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention. The bird's nest-like cage structure can also be seen in the STEM ADF photo. From the distribution diagram of each element, it can be seen that the elements Mo, O, Ni, Fe, and P are evenly distributed.
[0066] Figure 5 The OER performance test results of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention and the comparative example electrode material are shown in the figure. As can be seen from the figure, the electrode material of Example 1 has an OER performance of 10 mA / cm 2 The overpotential at the current density is 249 mV, which is much better than the overpotentials of Comparative Example 1 (345 mV), Comparative Example 2 (352 mV) and Comparative Example 3 (426 mV). 2 At a high current density, the overpotential is only 279 mV, which is much lower than the overpotential (530 mV) of the comparative example 1. This indicates that the OER performance of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in the embodiment 1 of the present invention is much better than that of the comparative example electrode material.
[0067] Figure 6 The OER cycle stability test results of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention are shown in Figure 1. It can be seen that after 12 hours of oxygen evolution performance test, its current density has no obvious change, indicating that the composite electrode material prepared by the method described in Example 1 of the present invention has good water electrolysis oxygen production cycle stability.
[0068] Figure 7The urea electro-oxidation performance test results of the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention and the comparative example electrode material are shown in the figure. As can be seen from the figure, the electrode material of Example 1 has a good electro-oxidation performance at 100 and 600 mA·cm -2 The overpotential for the oxidation of urea at different concentrations at a current density of is much lower than that of the comparative electrode material, indicating that the electrocatalytic oxidation removal performance of urea in aqueous solution by the bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention is much better than that of the comparative electrode material.
[0069] The bird's nest-shaped P,Fe-NiMoO4 self-supporting electrode material prepared by the method described in Example 1 of the present invention is used for the electro-oxidative degradation of H2S, drugs and organic dyes in aqueous solution, and also shows excellent electro-catalytic oxidation activity and stability. This shows that in addition to having excellent water electrolysis oxygen production performance, the electrode material prepared by the method described in the embodiment of the present invention can be used for the electro-catalytic oxidation purification of harmful substances such as H2S, drugs and organic dyes in industrial wastewater.
[0070] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, substitutions, simplifications, etc. made without departing from the principles and process of the present invention are equivalent replacements and should be included in the protection scope of the present invention.
Claims
1. A bird's nest-shaped P, Fe-NiMoO4 self-supporting electrode material and a preparation method thereof, characterized in that: The electrode material is a P,Fe-NiMoO4 with a bird's nest-like open structure composed of a P,Fe-co-doped NiMoO4 nanowire network grown in situ on nickel foam metal. The electrode material can be used for electrocatalytic oxidation oxygen evolution reaction of water and urea oxidation reaction in aqueous solution. The preparation method comprises the following steps: (1) Place nickel foam (1-10*1-10cm 2 )Use 1-3 mol·L -1 Ultrasonic treatment with dilute hydrochloric acid for 1-10 min, then treatment with acetone for 1-10 min, then washing with ethanol and drying; (2) (NH4)6Mo7O 24 ·4H2O and FeCl3·6H2O are dissolved in water and stirred evenly. (NH4)6Mo7O 24 4H2O concentration is 1-50mmol·L -1 , FeCl3·6H2O concentration is 10-100mmol·L -1 ; (3) The mixed solution obtained in step 2 is transferred to a polytetrafluoroethylene-lined autoclave, the nickel foam metal sheet treated in step 1 is placed vertically in the solution, and then reacted at 100-200° C. for 3-24 hours. After the autoclave is naturally cooled to room temperature, the nickel foam metal sheet is taken out, washed three times with deionized water and ethanol respectively, and dried to obtain a Fe-NiMoO4 sample; (4) In a tubular furnace, the Fe-NiMoO4 sample obtained in step (3) is placed in a porcelain boat, 0.1-2 g NaH2PO2·H2O is placed in another porcelain boat and placed upstream of the carrier gas, the tubular furnace is sealed, nitrogen carrier gas is introduced from one end, the temperature is increased to 250-450°C at a heating rate of 1-15°C / min, and the temperature is kept for 1-4 h to obtain a P,Fe-NiMoO4 sample.